Turning Scaling for Impact (S4I): Livestock productivity enhancement through improved forage technologies and a government partnership approach - Regassa, Bekele; Gudissa, Mulugeta; Ayele, Kalkidan; Mwendia, Solomon; Notenbaert, An (2025)
Livestock is an integral part of Ethiopian Agriculture contributing to food and nutrition, income, draft power, manure, transport, Gross Domestic Product (GDP) and social insurance. The sector serves as the nerve system for the country’s economic and social development through providing energy, resources and means to the mixed farm operation that is the backbone of the country’s economy. However, the sector is underdeveloped. To unlock the sector’s full potential, it is essential to identify critical gaps and implement targeted and strategic interventions. With over 70 million Cattle population, Ethiopia ranks 1st in Africa and 5th in the Globe. In contrast, in the 2025 Global hunger index, the country ranked 100th out of 123 countries indicating serious levels of hunger, where 19.7% of the population is undernourished, 35.5% of children under five are stunted, 6% of children under five are wasted and 4.6% of children die before their fifth birthday (GHI, 2025). Solving livestock feed related problems can shorten the path to economic and social development in Ethiopia. Hence, the Alliance of Bioversity international and CIAT (Alliance) and Ministry of Agriculture (MOA) have signed Lumpsum Funding Agreement (LFA) to contribute to feed development by bridging the gap between research and development with strategic, sequenced actions and through partnerships. Training of trainers (TOT) was facilitated in Hawassa town in August 2025 for 80 experts and development agents drawn from regional to kebele levels in collaboration with the MOA. The primary objective is to fill the livestock feed gaps by expanding the improved forages technology bundles through the CGIAR Science Program Scaling for Impact (S4I) by providing capacitating extension workers to subsequently train and assist livestock producers.